Palladium‐Aminopyridine Catalyzed C−H Oxygenation: Probing the Nature of Metal Based Oxidant. Issue 24 (5th November 2021) - Lubov, Dmitry P.; Bryliakova, Anna A.; Samsonenko, Denis G.; Sheven, Dmitriy G.; Talsi, Evgenii P.; Bryliakov, Konstantin P.
Abstract: A mechanistic study of direct selective oxidation of benzylic C(sp 3 )−H groups with peracetic acid, catalyzed by palladium complexes with tripodal amino‐ tris (pyriylmethyl) ligands, is presented. The oxidation of arylalkanes having secondary and tertiary benzylic C−H groups, predominantly yields, depending on the substrate and conditions, either the corresponding ketones or alcohols. One of the three 2‐pyriylmethyl moieties, which is pending in the starting catalyst, apparently, facilitates the active species formation and takes part in stabilization of the high‐valent Pd center in the active species, occupying the axial coordination site of palladium. The catalytic, as well as isotopic labeling experiments, in combination with ESI‐MS data and DFT calculations, point out palladium oxyl species as possible catalytically active sites, operating essentially via C−H abstraction/oxygen rebound pathway. For the ketones formation, O−H abstraction/ в ‐scission mechanism has been proposed. Abstract : Aliphatic C‐H activation : Palladium complexes with tripodal amino‐ tris (pyriylmethyl) ligands efficiently catalyze the oxidation of arylalkanes, having secondary and tertiary benzylic C−H groups, with peracetic acid. Depending on conditions, either the corresponding ketones or alcohols can be obtained as the major products. The catalytic and mechanistic results, in combination with computational data, point to palladium oxyl species as possible catalytically active sites, operating essentially via C−H abstraction/oxygen rebound pathway.